Hydrogen Bond Dynamic Properties of Ethanol-Methanol Mixtures Studied by The Complex Permittivity - Zhu Jia, Guo; Qing Yang, Xiao; Ma Huang, Ka (Asian Journal of Chemistry, 2011)
The complex permittivity of ethanol-methanol mixtures, over the entire concentration range, have been measured using resonant cavity perturbation method at 293, 303 and 313 K. The observed values of the permittivity gradually increased with increasing concentration of methanol in ethanol, whereas the relaxation time decreased with increasing concentration and temperature. The increase in the dielectric relaxation time in ethanol-methanol mixtures is attributed to the spatial constraints of ethanol molecules on the hydrogen-bond network, the reorientation processes in pure liquids and mixtures are controlled by enthalpic rather than by entropic factors.